Characteristics and impact of mesoscale eddies in the eastern tropical North Atlantic - Schütte, Florian (2016)
A combination of multiple ocean observing system elements is used to assess the mesoscale eddy activity in the tropical Atlantic off northwestern Africa (12-22°N and 15-26°W). Considering just the rotation direction of the surface flow field, eddies are categorized into cyclonic (CEs) and anticyclonic eddies. If vertical stratification is considered additionally, a refinement can be made by distinguishing between anticyclonic (AEs) and anticyclonic modewater eddies (ACMEs). ACMEs are characterized by a subsurface mode of rather homogenous water located between upward and downward displaced isopycnals. Eddies can be identified and classified from space by investigating the sea surface parameters: Sea level anomaly (SLA), sea surface temperature (SST) and sea surface salinity (SSS). AEs/CEs are associated with an elevation/depression of SLA and enhanced/reduced SST and SSS in their cores. However, 20% of all anticyclonic eddies are associated with reduced SST and SSS instead and are identified as ACMEs. In the area of interest, about 146±4 eddies per year with a minimum lifetime of 7 days are identified (52% CEs, 39% AEs, 9% ACMEs). All observed eddies are isolated and serve as transport agents, exporting water from the coast into the open ocean. In CEs and ACMEs low oxygen cores are identified and related to enhanced primary production at the surface and an associated elevated respiration rates within the isolated eddy cores. It could be observed that the phase speed of NIWs and the speed of the mean eddy flow are of similar magnitude. Therefore, critical layer formation is expected and mixing is likely to occur close to the euphotic zone at the eddy periphery. These processes describe one mechanism that support an upward nutrient flux towards the euphotic zone and the coexistence with a highly isolated eddy core. The analysis shows that anomalous environments associated with eddy cores occur more frequently than previously expected. In dieser Studie wurden die Eigenschaften mesoskaliger Wirbel im tropischen ...